2017
DOI: 10.1093/infdis/jix154
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Immunogenicity of 2-dose Human Papillomavirus 16/18 AS04-adjuvanted Vaccine Schedules in Girls Aged 9–14 Years: A Randomized Trial

Abstract: SummaryHuman papillomavirus vaccination began using a 3-dose schedule. Compared with the 3-dose schedule in women, the 2-dose schedules are effective options in young girls as of 36 months after first dose. Two-dose schedules could improve compliance and vaccination coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…This is consistent with previous findings reported by Romanowski et al, which showed that 2 doses of bHPV (spaced at 6 months) produced an immune response that persists for up to 5 years of follow-up [ 10 ]. Although our antibody responses differ slightly from those reported by Romanowski et al [ 10 ] and Huang et al [ 12 ], who used the same serological assay, our findings support evidence of the high and strong immune response in girls who received <3 doses. In comparing antibody response among different studies, it should be taken into account the difference in participants and study designs, as well as differences between laboratories and kit lots for VLP-based ELISAs.…”
Section: Discussionsupporting
confidence: 66%
“…This is consistent with previous findings reported by Romanowski et al, which showed that 2 doses of bHPV (spaced at 6 months) produced an immune response that persists for up to 5 years of follow-up [ 10 ]. Although our antibody responses differ slightly from those reported by Romanowski et al [ 10 ] and Huang et al [ 12 ], who used the same serological assay, our findings support evidence of the high and strong immune response in girls who received <3 doses. In comparing antibody response among different studies, it should be taken into account the difference in participants and study designs, as well as differences between laboratories and kit lots for VLP-based ELISAs.…”
Section: Discussionsupporting
confidence: 66%
“…The reduced dose schedule from 3-dose to 2-dose for the young adolescent population was based on the evidence that the 2-dose regimens in young adolescent girls showed an equivalent immune response to the 3-dose regimen in 15-25 years old females in terms of magnitude and durability of the immune response. 40,41 Studies following vaccinated individuals for 6-12 years suggested that 3-dose HPV vaccines offer long-term protection against HPV infection and HPVrelated diseases. [42][43][44] However, whether the duration of protection can cover the entire sexually active life expectancy and whether a boost dose is required remained to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials in pediatric populations are conducted in those individuals who stand to potentially benefit from the treatment. Healthy children participate in studies such as immunization trials against diseases that they might reasonably be expected to contract or postapproval assessment of nutritional supplements . Reasonably stable children with the target disease participate in clinical pharmacology studies as well as in clinical studies of medications used to treat diseases that occur only in children .…”
Section: General Study Considerations For Pediatric Subjectsmentioning
confidence: 99%